(untitled) (Shahid Kirti Multidisciplinary Journal, 2026)
Financial independence has become an important factor influencing psychological well-being among emerging adults by providing them the flexibility to make economic decisions against the background of unstable economic conditions and paucity of institutional aid. However, while the existing literature has established a link between financial conditions and psychological well-being, little is understood regarding the underlying psychological mechanisms of the translated effect of multidimensional financial independence on psychological well-being, in particular, in the context of emerging economies. Building on the existing literature on Self-Determination Theory, Conservation of Resources Theory, and Future Time Perspective Theory, the present study aims to relate financial independent to psychological well-being by investigating the impact of future orientation as a psychological mechanism. The present study uses a survey data from a sample of 207 students and alumni of Tribhuvan University, Kathmandu, Nepal, enrolled in undergraduate and postgraduate programs. With correlation, regression, and Hayes’ PROCESS macro, a mediation analysis was conducted. An analysis of variance showed that individuals’ financial preparedness, saving and invest behavior, household consumption, and wealth accumulation significantly influenced psychological well-being. Furthermore, future orientation partially mediating these dimensions of financial independence and emotional well-being suggests future orientation as a psychological mechanism of the study. This study adds to the existing financial psychology and well-being corpus through this mechanism-based, comprehensive understanding of financial independence among emerging adults in an understudied economy of emerging countries. From the practical viewpoint, our study also acknowledges the significance of incorporating futurist thinking into the existing modules focusing on financial literacy and the development of the youth to increase their financial and psychological well being.